Developing Enterprise Social Software in China: Insights from Mingdao. Issue 2 (November 2017) - Le-Nguyen, Khuong; Guo, Yue; Qiong, Jia
Cloud-computing and Web 2.0 technologies have triggered a new wave of IT infrastructure adoption, which has been radically changing the way we live and work. In particular, Enterprise 2.0 and Enterprise Social Software (ESS) are getting more attention from organizations worldwide as they help staff to work and collaborate more efficiently. In this paper, we introduce the case of a leading firm in China called Mingdao that provides an ESS platform via the SaaS delivery model. Our teaching case gives insights into how Mingdao experienced its platform's early tortuous design and development, defined its business and revenue model, and improved its platform's various functions and features. Such organizational experiences not only reflect the opportunities and challenges of the ESS market in China, but also present a new way of communication, collaboration, and sharing on the enterprise social network platform. This case also has implications for practitioners for how cloud-computing and Web 2.0 technology can drive the transformation of both enterprise and management as well as how the ESS platform could help accelerate knowledge management activities across the organization.